The Influence of Transformational Leadership Style and Work Motivation on Employee Performance at Religious Court Office Sinjai District - Nurfaaizah; Chalid Imran Musa; Zainal Ruma; Agung Widhi Kurniawan; Uhud Darmawan Natsir (Economics and Business Journal (ECBIS), 2023)
This study aims to find out how the influence of transformational leadership style and work motivation on employee performance at the Sinjai District Religious Court Office. The population and this study were 40 employees of the Sinjai District Religious Court. Data collection was carried out using the method of interviews, documentation and distribution of questionnaires. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS).